Antirheumatoid Arthritic Effects of Sabia parviflora Wall. Leaf Extracts via the NF-κB Pathway and Transient Receptor Potential Protein Family - Zhou, Yongqiang; Zhao, Yamin; Xu, Hui; Zhao, Xiaoyan; Zhao, Chunli; Zhou, Tao; Zhang, Yongping (Frontiers in Pharmacology, 2022)
As an important traditional medicine of Buyi and Miao ethnic groups in Guizhou, Sabia parviflora Wall. provides antiviral properties against hepatitis, eliminates wind and dampness, and exhibits anti-inflammatory and pain relief properties. It has also been shown to treat rheumatoid arthritis (RA) and other diseases. However, the pharmacodynamic mechanism of S. parviflora Wall. for RA has not been reported. In this study, we identified the effective compounds of S. parviflora Wall. leaves against RA and discussed the mechanism against complete Freund’s adjuvant-induced arthritis (AIA) based on inflammatory protein and transient receptor potential (TRP) protein. S. parviflora Wall. leaf extracts (0.64 g/kg, 0.32 g/kg and 0.16 g/kg, once daily) were given orally for 21 d. On the 15th day of complete Freund’s adjuvant-induced RA, the effects of this medicine on RA rats were investigated. S. parviflora Wall. extracts increased body weight, decreased foot swelling, and reduced thymus and spleen indices in model rats. Most of pannus in the synovial tissue of RA rats disappeared upon treatment, and the local inflammatory cells were greatly reduced when given the fraction of n-butanol (0.64 g/kg/d, 0.32 g/kg/d and 0.16 g/kg/d) of 70% alcohol soluble fraction of S. parviflora Wall. leaves. In addition, the release of inflammatory factors tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-10 (IL-10), interleukin-15 (IL-15), and vascular endothelial growth factor (VEGF) in RA rat serum was inhibited. The active compounds inhibited the expression of TNF-α, IL-1β, IL-6, IL-10, IL-15, and nuclear factor kappa-Bp65 (NF-κBp65) inflammatory protein and TRP protein transient receptor potential melastatin-5 (TRPM-5) and transient receptor potential channel-6 (TRPC-6), to reduce the expression of VEGF in synovial tissue of RA rats and relieve redness and edema. High-performance liquid chromatography identified six flavonoids and three triterpenoid saponins as active compounds. These findings suggest S. parviflora Wall. leaves may play a role in RA treatment by inhibiting the release of inflammatory factors, as well as participating in the inflammatory protein expression in the NF-κB pathway and TRP protein family.